Strategi Komunikasi Pemasaran pada Rebranding Usaha Kuliner Kopi - Nayla Rachmi; Rini Rinawati (Bandung Conference Series: Communication Management, 2023)
Abstract. In a rebranding there are several stages in the form of renaming, relaunching, redesigning, repositioning. At the rebranding stage carried out by a business, a marketing communication strategy is needed, one of which is to be able to maintain a business so that purchases and brand awareness occur. The purpose of this research is to find out the marketing communication strategy used by Jatinangor Coffee in relaunching Jatinangor House, to find out the inhibiting factors for Jatinangor Coffee's marketing communication strategy in rebranding and to determine the supporting factors for Jatinangor Coffee's marketing communication strategy in rebranding. This study uses a qualitative research method with a case study approach. The result of this research is the existence of a marketing communication strategy that is carried out by Jatinangor House in conducting a re-launch, namely maximizing the use of several Instagram social media features, collaborating with coffee review instagram accounts, collaborating with online sales media and providing the maximum possible service on sales. direct . In the marketing strategy communication that finds, the discovery of obstacles in the form of competitors, but these obstacles are overcome by continuing to follow the competition by continuously presenting new innovations. In addition to the obstacles found, Jatinangor House also found supporting factors in the form of promotions that were obtained free of charge from the public who provided reviews in the form of product coverage on Jatinangor House's social media. Abstrak. Dalam suatu rebranding terdapat beberapa tahapan yang berupa renaming, relaunching, redesigning, repositioning. Pada tahapan rebranding yang dilakukan oleh suatu usaha, diperlukan suatu strategi komunikasi pemasaran yang salah satunya dimaksudkan untuk dapat mempertahankan suatu usaha agar terjadinya pembelian dan kesadaran merk. Tujuan penelitian Untuk mengetahui strategi komunikasi pemasaran yang dilakukan Jatinangor Coffe dalam melakukan relaunching menjadi Jatinangor House, untuk mengetahui faktor penghambat strategi komunikasi pemasaran Jatinangor Coffe dalam melakukan rebranding dan untuk mengetahui faktor pendukung strategi komunikasi pemasaran Jatinangor Coffe dalam melakukan rebranding. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus. Hasil dari penelitian ini adalah adanya strategi komunikasi pemasaran yang dilakukan Jatinangor House dalam melakukan relaunching yaitu memaksimalkan penggunaan pada beberapa fitur media sosial instagram, melakukan kerja sama dengan akun instagram ulasan kopi, melakukan kerja sama dengan media penjualan online dan melakukan pelayanan semaksimal mungkin pada penjualan langsung. Pada strategi komunikasi pemasaran yang dilakukannya, ditemukan hambatan berupa hadirnya pesaing, tetapi hambatan tersebut tentunya diatasi dengan terus mengikuti persaingan dengan teru menghadirkan inovasi baru. selain hambatan yang ditemukan, jatinangor house juga menemukan faktor pendukung berupa adanya promosi yang didapatkan secara gratis dari masyarakat yang memberikan ulasan berupa liputan produknya pada media s osial jatinangor house.